Burkina Faso : Staff Report for the 2011 Article IV Consultation and the Third Review Under the Extended Credit Facility: Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burkina Faso. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This 2011 Article IV Consultation and the Third Review Under the Extended Credit Facility for Burkina Faso highlights that the authorities have maintained fiscal consolidation efforts while mitigating the impact of exogenous shocks. Executive Directors have welcomed the authorities' sustained implementation of sound policies and structural reforms, which has contributed to robust economic growth, low inflation, and a broadly favorable external position. Directors have encouraged the authorities to maintain fiscal discipline within the context of a medium-term fiscal framework while increasing investment and social spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet